2022
DOI: 10.1155/2022/2090560
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression Network Analysis-Based Identification of Critical Genes Differentiating between Latent and Active Tuberculosis

Abstract: Background and Objectives. The identification of reliable biomarkers is critical to the diagnosis and prevention of progression from latent tuberculosis infection (LTBI) to active tuberculosis (ATB). This study was thus developed to identify key hub genes capable of differentiating between LTBI and ATB through a weighted gene coexpression network analysis (WGCNA) approach. Methods. Three Gene Expression Omnibus (GEO) microarray datasets (GSE19491, GSE98461, and GSE152532) were downloaded, with GSE19491 and GSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Therefore, targeting OS to restore redox homeostasis in IVD cells and thus improve IVDD is considered a promising therapeutic approach ( In our research, we comprehensively evaluated the role of oxidative stress-related genes (OSRGs) in the diagnosis and subtype classi cation of IVDD based on the Gene Expression Omnibus (GEO). Then we built a nomogram model for the six core OSRGs (ATP7A, MELK, NCF1, NOX1, RHOB, and SP1) to predict the prevalence of IVDD (Chen et al, 2022;Wu et al, 2022). Finally, we developed different OSRG clusters and gene clusters and found that they are in agreement with the expression landscape of IVDD-related genes, which suggests that OSRGs could be exploited for early diagnosis and classi cation of IVDD.…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, targeting OS to restore redox homeostasis in IVD cells and thus improve IVDD is considered a promising therapeutic approach ( In our research, we comprehensively evaluated the role of oxidative stress-related genes (OSRGs) in the diagnosis and subtype classi cation of IVDD based on the Gene Expression Omnibus (GEO). Then we built a nomogram model for the six core OSRGs (ATP7A, MELK, NCF1, NOX1, RHOB, and SP1) to predict the prevalence of IVDD (Chen et al, 2022;Wu et al, 2022). Finally, we developed different OSRG clusters and gene clusters and found that they are in agreement with the expression landscape of IVDD-related genes, which suggests that OSRGs could be exploited for early diagnosis and classi cation of IVDD.…”
Section: Introductionmentioning
confidence: 90%